2021
DOI: 10.1111/jnu.12712
|View full text |Cite
|
Sign up to set email alerts
|

The effect of music interventions on chronic pain experienced by older adults: A systematic review

Abstract: Older adults are at high risk of developing chronic pain, recognized as pain that persists or recurs for more than 3 months (American Chronic Pain Association [ACPA], 2019;Treede et al., 2015). Chronic pain in older adults is often associated with an increased incidence of adverse outcomes such as physical disability, anxiety, depression, suicide, a lower quality of life, and sleep impairment (Mills et al., 2019). Distinct from acute pain, which is of short duration and is expected to stop once the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…Sample size estimation was based on the effect and standard variation found in the systematic review ( Hsu et al, 2022 ), and was conducted with G*power 3.1 ( Faul et al, 2009 ) setting α = 0.05 and β = 0.20. It was found that 17 participants were needed in each group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample size estimation was based on the effect and standard variation found in the systematic review ( Hsu et al, 2022 ), and was conducted with G*power 3.1 ( Faul et al, 2009 ) setting α = 0.05 and β = 0.20. It was found that 17 participants were needed in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Among various non-pharmacological interventions, music interventions are widely used for chronic pain relief due to their advantages such as inexpensive, non-discriminatory, and non-adverse effects ( Sihvonen et al, 2017 ). A growing body of evidence supports the use of music interventions for pain management ( Martin-Saavedra et al, 2018 ; Howlin and Rooney, 2021 ; Hsu et al, 2022 ). Hsu et al (2022) implemented a music intervention in 66 elderly patients with osteoarthritis, and the visual analog scales (VAS) scores were significantly lower in the intervention group than in the control group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers can help the care recipient engage with music, photos, books, videos, and hobbies to capture their attention and distract them from pain. 17 Aromatherapy can soothe discomfort in older adults who have intact olfactory senses. 18 These noninvasive, lowcost approaches can be used alone or in combination with other strategies.…”
Section: Lowerrisk Approaches To Managing Painmentioning
confidence: 99%
“…Previous studies have tried to find methods to reduce pain and discomfort during colposcopy to improve treatment outcomes such as lidocaine injection, lidocaine spray, or forced coughing [ 8 , 9 , 10 , 11 ]. Music has been investigated in chronic pain, pain reduction in children, and other procedures such as orthopedic surgery or cystoscopy with promising outcomes [ 12 , 13 , 14 , 15 ]. Several studies have recently been conducted that addressed the effect of listening to music on pain and discomfort reduction during colposcopy [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%